2003
DOI: 10.1520/jfs2002426
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling of 3,4 Methylenedioxymethamphetamine (MDMA) Tablets Seized in Hong Kong

Abstract: During 2000During -2001 the Government Laboratory of Hong Kong received over 600,000 ecstasy tablets in more than 2,600 cases. Using GC-MS or FTIR, the major amphetamine-type stimulants were identified, and the samples were categorized into four groups containing: (1) 3,4methylenedioxymethamphetamine (MDMA), (2) methamphetamine (MA), (3) 3,4-methylenedioxyamphetamine (MDA), or (4) amphetamine. Our study revealed that in Hong Kong MDMA tablets have made up 98 and 71% of the total ecstasy tablets examined in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…All ecstasy users in our study reported an orange appearance of the tablets taken during the period of 2000 through 2001. As reported by Cheng et al (2003), ecstasy tablets in Hong Kong during this time period contain approximately 50% MDMA, with ketamine as a common additive in these tablets.…”
Section: Participantssupporting
confidence: 52%
“…All ecstasy users in our study reported an orange appearance of the tablets taken during the period of 2000 through 2001. As reported by Cheng et al (2003), ecstasy tablets in Hong Kong during this time period contain approximately 50% MDMA, with ketamine as a common additive in these tablets.…”
Section: Participantssupporting
confidence: 52%
“…Therefore, structure elucidation of MDMA impurities was studied for various routes: reductive amination [4], nitropropene [5], Leuckart [5,6], or bromopropane [6,7]. Besides, some authors focused on the analysis of impurities found in illicit tablets [8][9][10][11][12][13] and tried to correlate them to a specific synthesis route.…”
Section: Introductionmentioning
confidence: 99%
“…These tablets generally contain such amphetamine-type stimulants (ATS) as 3,4-methylenedioxymethamphetamine (MDMA), methamphetamine (MA), 3,4-methylenedioxyamphetamine (MDA) and amphetamine as the active ingredients (Cheng et al 2003). The latter two are however less prevalent in locally seized materials.…”
Section: Introductionmentioning
confidence: 99%